Comparison of dynamic responses of cellular metabolites in escherichia coli to pulse addition of substrates - Merican, A.F.; Hoque, M.A.; Fard, A.T.; Rahman, M.; Alattas, O.; Akazawa, K. (2011)
We conducted an integrated study of cell growth parameters, product formation, and the dynamics of intracellular metabolite concentrations using Escherichia coli with genes knocked out in the glycolytic and oxidative pentose phosphate pathway (PPP) for glucose catabolism. We investigated the same characteristics in the wild-type strain, using acetate or pyruvate as the sole carbon source. Dramatic effects on growth parameters and extracellular and intracellular metabolite concentrations were observed after blocking either glycolytic breakdown of glucose by inactivation of phosphoglucose isomerase (disruption of pgi gene) or pentose phosphate breakdown of glucose by inactivation of glucose-6-phosphate dehydrogenase (disruption of zwf gene). Reducing power (NADPH) was mainly produced through PPP when the pgi gene was knocked out, while NADPH was produced through the tricarboxylic acid (TCA) cycle by isocitrate dehydrogenase or NADP-linked malic enzyme when the zwf gene was knocked out. As expected, when the pgi gene was knocked out, intracellular concentrations of PPP metabolites were high and glycolytic and concentrations of TCA cycle pathway metabolites were low. In the zwf gene knockout, concentrations of PPP metabolites were low and concentrations of intracellular glycolytic and TCA cycle metabolites were high.